Analysis of Online Fraud Crimes in Buying and Selling Roblox Accounts on Social Media (Facebook) Based on the ITE Law - Safitri Handayani; Sri Pramudya Wardhani (International Journal of Science and Environment (IJSE), 2026)
The development of information technology and the increasing popularity of online games, particularly Roblox, have led to the emergence of the practice of buying and selling game accounts through social media such as Facebook. These transactions are generally conducted informally without adequate legal protection mechanisms, thus opening up opportunities for fraud. This study aims to analyze the types of fraud that occur in the buying and selling of Roblox accounts on Facebook and examine the criminal sanctions stipulated in "Law Number 1 of 2024 concerning Electronic Information and Transactions." Identifying the specific fraud schemes employed and evaluating the criminal penalties imposed by the ITE Law in relation to the concepts of legal protection and legal certainty are the primary concerns of this study. Using a literature review of laws, scientific publications, and other legal materials, this study follows a normative legal research methodology that draws on conceptual and statutory sources. The study findings indicate that the dominant fraud modes include social engineering, non-delivery fraud, the use of fake identities, and account reclaim, which result in material losses in the form of the loss of digital assets of economic value. In addition, the act fulfills the elements of a criminal act as regulated in "Article 28 paragraph (1), Article 30, Article 32, and Article 36 of the ITE Law". This study concludes that the ITE Law has provided a basis for legal certainty and legal protection for victims of digital transaction fraud, but it is still necessary to strengthen law enforcement and digital literacy in society.